Ensuring Integrity in Governments' Response to COVID-19 - World Bank Group (World Bank, Washington, DC, 2020)
Governments around the world are designing and implementing rapid responses to the COVID-19 (coronavirus) pandemic. In this effort, they are faced with three extraordinary challenges: (1) a public health emergency to contain the virus including identifying and treating infected populations; (2) widespread food and livelihood insecurity due to mandated stoppage of economic activity and the resulting disruption of food supplies; and (3) adoption of emergency powers to address the crises and maintain public safety. Corruption risks, present in government responses to all these challenges and heightened by the scale and speed of the emergency, undermine the effectiveness of responses. The strains placed on the public sector in responding to emergencies present enormous opportunities for corruption to flourish. Corruption can lead to theft, waste and misuse of scarce resources, resulting in unnecessary suffering and death. It can also entrench elite privilege and inequality and undermine institutions of accountability with lasting consequences. Governments face the additional challenge of maintaining continuity in core functions while dealing with these exceptional circumstances. This note provides guidance on addressing and mitigating corruption risks in the COVID-19 (coronavirus) response, both in the initial response and in the medium term. Over time, and as we learn more about the impact and effectiveness of responses to the crisis, it will be essential to adjust anticorruption efforts to support new governance arrangements and give greater attention to addressing impunity for misbehavior, as well as to shaping norms and standards that affect public sector performance and behavior. The note identifies the broad areas of government response where corruption risks are present and heightened in the context of a pandemic emergency, describes the types of risks that are likely to arise, and provides recommendations for addressing and mitigating them. Guidance provided in this note should be read in combination with the other pieces on the Governance and Institutional Response to the COVID-19 (coronavirus) Pandemic.